Attenuation of Collagen-Induced Arthritis in Rat by Nicotinic Alpha7 Receptor Partial Agonist GTS-21. (27th February 2014) - Hu, Yiping; Liu, Ruoxi; Li, Jinchao; Yue, Ye; Cheng, Wenxiang; Zhang, Peng
Abstract : This research was performed to observe the effect of GTS-21 on Collagen Induced Arthritis (CIA). CIA model was used and after the onset of arthritis, the rats were divided into three groups based on their clinical symptoms score. Two groups were intraperitoneally (IP) injected daily with GTS-21 (1 mg/kg, 2.5 mg/kg) for a week, whereas phosphate buffered saline (PBS) was used for the control group. Cytokine titers, radiological, and histological examinations were performed at different time points after treatment with GTS-21. Compared with those of the control, the levels of TNF- α, IL-1, and IL-6 in the serum were significantly reduced after GTS-21 management. In addition, radiological results show that bone degradation was inhibited as well. Moreover, the hematoxylin and eosin (H&E) staining indicated that the histological score was significantly alleviated in the therapeutic group. Tartrate-resistant acid phosphatase (TRAP) stain-positive cells were also detected in the destruction of the articular cartilage, which was significantly reduced compared with the control group. This study provides the first evidence on the effect of GTS-21 as a potential treatment for RA.